Simultaneous targeting of EGFR, HER2, and HER4 by afatinib overcomes intrinsic and acquired cetuximab resistance in head and neck squamous cell carcinoma cell lines. Issue 6 (1st May 2018) - De Pauw, Ines; Lardon, Filip; Van den Bossche, Jolien; Baysal, Hasan; Fransen, Erik; Deschoolmeester, Vanessa; Pauwels, Patrick; Peeters, Marc; Vermorken, Jan Baptist; Wouters, An
Abstract : The epidermal growth factor receptor (EGFR, HER1) is a therapeutic target in head and neck squamous cell carcinoma (HNSCC). After initial promising results with EGFR‐targeted therapies such as cetuximab, therapeutic resistance has become a major clinical problem, and new treatment options are therefore necessary. Moreover, the relationship between HER receptors, anti‐EGFR therapies, and the human papillomavirus (HPV) status in HNSCC is not fully understood. In contrast to first‐generation EGFR inhibitors, afatinib irreversibly inhibits multiple HER receptors simultaneously. Therefore, treatment with afatinib might result in a more pronounced therapeutic benefit, even in patients experiencing cetuximab resistance. In this study, the cytotoxic effect of afatinib as single agent and in combination with cisplatin was investigated in cetuximab‐sensitive, intrinsically cetuximab‐resistant, and acquired cetuximab‐resistant HNSCC cell lines with different HPV status under normoxia and hypoxia. Furthermore, the influence of cetuximab resistance, HPV, and hypoxia on the expression of HER receptors was investigated. Our results demonstrated that afatinib was able to establish cytotoxicity in cetuximab‐sensitive, intrinsically cetuximab‐resistant, and acquired cetuximab‐resistant HNSCC cell lines, independent of the HPV status. However, cross‐resistance between cetuximab and afatinib might be possible. Treatment with afatinib caused a G0 /G1 cell cycle arrest as well as induction of apoptotic cell death. Additive to antagonistic interactions between afatinib and cisplatin could be observed. Neither cetuximab resistance nor HPV status significantly influenced the expression of HER receptors in HNSCC cell lines. In contrast, the expression of EGFR, HER2, and HER3 was significantly altered under hypoxia. Oxygen deficiency is a common characteristic of HNSCC tumors, and these hypoxic tumor regions often contain cells that are more resistant to treatment. However, we observed that afatinib maintained its cytotoxic effect under hypoxia. In conclusion, our preclinical data support the hypothesis that afatinib might be a promising therapeutic strategy to treat patients with HNSCC experiencing intrinsic or acquired cetuximab resistance. Abstract : Inhibition of aberrant epidermal growth factor receptor (EGFR) signaling by cetuximab improves overall survival in head and neck squamous cell carcinoma (HNSCC). However, drug resistance is a major clinical problem. Cetuximab resistance may arise from enzymatic activity of other HER receptors besides EGFR. We demonstrate that irreversible inhibition of multiple HER receptors by afatinib is a promising novel therapeutic strategy to treat patients with HNSCC experiencing cetuximab resistance.